Does Digital Transformation of Government Lead to Enhanced Citizens’ Trust and Confidence in Government? - Mahmood, Mohamed. author. aut Link
XVII, 149 p. 11 illus., 6 illus. in color.
Keywords: This research contributes to the growing body of knowledge as well as offers significant theoretical contributions and policy implications. As far as the researcher’s knowledge, this is the first research of its type that investigates the relationship between digital enabled transformation of government and citizens’ trust & confidence in government. The proposed conceptual model also makes a novel contribution at a conceptual level, which can be used as a frame of reference by researchers as well as practitioners when planning ICT-enabled transformation projects in government. The context of the research is the Kingdom of Bahrain, the top-ranked country in ICT adoption in the Gulf Cooperation Council (GCC) region.